EKSPLORASI MODEL TRANSFORMASI SDM UMKM MALANG RAYA DALAM MEWUJUDKAN EKONOMI DIGITAL DAN HIJAU: Transformasi SDM, Ekonomi Hijau, Keberlanjutan Bisnis, Kapabilitas SDM, Strategi Adaptasi - Askiyanto, Moh; Fitria Hayuningtyas, Ruri; Audiva, Rizki (Jurnal Paradigma Ekonomika, 2025)
Human resource readiness is a critical factor in the success of this transformation; however, various obstacles remain, including limited digital skills, a lack of understanding of green economy principles, and limited access to technology and funding. This study focuses on identifying the factors that influence human resource readiness in MSMEs in adapting to technological advances and sustainability policies. Using a quantitative approach, this study utilises case studies from several SMEs in the Malang region. Data collection was conducted through in-depth interviews with SME operators and policymakers, direct observations, and analysis of policy documents related to digital transformation and the green economy. The collected data will be analysed using thematic analysis to identify patterns and effective strategies for strengthening SME human resources. The research findings indicate that human resource readiness has a significant impact on enhancing SME competitiveness. Competent human resources who are adaptable to technological changes and understand the principles of the green economy have proven capable of driving business transformation toward a more modern and sustainable direction. Digital literacy enables SMEs to access broader markets.